The Urgency of Determining Accurate Costing Methods in the Cost of Goods Manufactured - Rohma, Frida Fanani; Sholihah (Neo Journal of economy and social humanities, 2022)
The mechanism for determining product cost is a crucial factor because it can impact sales volume and profit. One of the control mechanisms in determining the cost of goods manufactured is to use the concept of accurate costing. Thus, this study aim to analysis the use of an accurate costing method to minimize errors in determining the cost of goods manufactured. This study uses a literature review with charting the field technique. The results show that each method of assigning costs has its accuracy according to the type of cost charged to the product. Direct costs are assigned to cost objects by direct tracing. Meanwhile, costs that require driving activities are charged using driver tracing. Meanwhile, costs that do not have a causal relationship to the cost object are charged with allocation. The result shows that Activity Based Costing (ABC) is rated as the most accurate method. However, it should be noted that the accuracy of ABC depends on the ability of resources to identify cost drivers. Failure to identify cost drivers can be a boomerang that makes ABC's effectiveness lower than conventional methods.